Studi Pendugaan Sisa Usia Guna Waduk Sutami Dengan Pendekatan Sedimentasi - Fidari, Jadfan Sidqi; Bisri, Mohammad; Suhartanto, Ery (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2013)
Sutami Dam is a dam with the largest reservoir with managed by Perum Jasa Tirta I. This reservoir has been operating for more than 39 years (operates in 1972 and using reference to recent data in 2011). This study was performed to determine the trend of sediment discharge and reservoir live time in order to find out how the rest of the remaining Sutami reservoir for reservoir operations. Data analysis is used as the data for 6 years period and in 1972 data for comparison. Point source of sediment in the reservoir is divided into two points, Sutami sediments by direct inflow to the the Sutami Reservoir (Metro River) and outflow from Sengguruh Reservoirs (Brantas River and Lesti River). The third point is the calculation of sediment discharge to determine the most influential point sediment carrier in Sutami Reservoir. Reservoir live time to the rest of Sutami calculated using three methods of approach. Volume approach, elevation approach, and empirical approaches. 2 Tanpa nomer halaman The point that has the most impact is of the Brantas River (inflow from Sengguruh Reservoir) with Qs = 2.27 kg/sec (2011), then from the Metro River with Qs = 1.97 kg/sec (2011). ). Based on the analysis of the remaining life time for Sutami Reservoir using three methods of approach, it is known to Sutami Reservoir live time trends tend to decrease. Elevation control point (+233.3 m) with elevation approach and volume approach gives results for the remaining life of 5 years and 1.5 years, while the empirical approach with 97% trap efficiency give results 9 years for the remaining life time of Sutami Reservoir.Key words: Sutami Reservoir, Sedimentation, Reservoir Live Time